Geological setting and a geometallurgical evaluation of the Namakwa Sands heavy minerals deposit, West Coast of South Africa - Philander, Carlo (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.